MINERALOGICAL AND STABLE ISOTOPE STUDIES OF GOLD–ARSENIC MINERALISATION IN THE SAMS CREEK PERALKALINE PORPHYRITIC GRANITE, SOUTH ISLAND, NEW ZEALAND - Faure K.; Brathwaite R.L. (My University, 2006)
At Sams Creek, a gold-bearing, peralkaline granite porphyry dyke, which has a 7 km strike length and is up to 60 m in thickness, intrudes camptonite lamprophyre dykes and lower greenschist facies metapelites and quartzites of the Late Ordovician Wangapeka formation. The lamprophyre dykes occur as thin (< 3 m) slivers along the contacts of the granite dyke. δ18Omagma values (+5 to +8‰, VSMOW) of the A-type granite suggest derivation from a primitive source, with an insignificant mature crustal contribution. Hydrothermal gold–sulphide mineralisation is confined to the granite and adjacent lamprophyre; metapelite country rocks have only weak hydrothermal alteration. Three stages of hydrothermal alteration have been identified in the granite: Stage I alteration (high fO2) consisting of magnetite–siderite±biotite; Stage II consisting of thin quartz–pyrite veinlets; and Stage III (low fO2) consisting of sulphides, quartz and siderite veins, and pervasive silicification. The lamprophyre is altered to an ankerite–chlorite–sericite assemblage. Stage III sulphide veins are composed of arsenopyrite + pyrite ± galena ± sphalerite ± gold ± chalcopyrite ± pyrrhotite ± rutile ± graphite. Three phases of deformation have affected the area, and the mineralised veins and the granite and lamprophyre dykes have been deformed by two phases of folding, the youngest of which is Early Cretaceous. Locally preserved early-formed fluid inclusions are either carbonic, showing two- or three-phases at room temperature (liquid CO2-CH4 + liquid H2O ± CO2 vapour) or two-phase liquid-rich aqueous inclusions, some of which contain clathrates. Salinities of the aqueous inclusions are in the range of 1.4 to 7.6 wt% NaCl equiv. Final homogenisation temperatures (Th) of the carbonic inclusions indicate minimum trapping temperatures of 320 to 355°C, which are not too different from vein formation temperatures of 340–380°C estimated from quartz–albite stable isotope thermometry. δ18O values of Stage II and III vein quartz range from +12 and +17‰ and have a bimodal distribution (+14.5 and +16‰) with Stage II vein quartz accounting for the lower values. Siderite in Stage III veins have δ18O (+12 to +16‰) and δ13C values (−5‰, relative to VPDB), unlike those from Wangapeka Formation metasediments (δ13Cbulk carbon values of −24 to −19‰) and underlying Arthur Marble marine carbonates (δ18O = +25‰ and δ13C = 0‰). Calculated δ18Owater (+8 to +11‰, at 340°C) and $\delta^{13}{\text{C}}_{{\rm CO}_{2}}$ (−5‰) values from vein quartz and siderite are consistent with a magmatic hydrothermal source, but a metamorphic hydrothermal origin cannot be excluded. δ34S values of sulphides range from +5 to +10‰ (relative to CDT) and also have a bimodal distribution (modes at +6 and +9‰, correlated with Stage II and Stage III mineralisation, respectively). The δ34S values of pyrite from the Arthur Marble marine carbonates (range from +3 to +13‰) and Wangapeka Formation (range from −4 to +9.5‰) indicate that they are potential sources of sulphur for sulphides in the Sams Creek veins. Another possible source of the sulphur is the lithospheric mantle which has positive values up to +14‰. Ages of the granite, lamprophyre, alteration/mineralisation, and deformation in the region are not well constrained, which makes it difficult to identify sources of mineralisation with respect to timing. Our mineralogical and stable isotope data does not exclude a metamorphic source, but we consider that the source of the mineralisation can best be explained by a magmatic hydrothermal source. Assuming that the hydrothermal fluids were sourced from crystallisation of the Sams Creek granite or an underlying magma chamber, then the Sams Creek gold deposit appears to be a hybrid between those described as reduced granite Au–Bi deposits and alkaline intrusive-hosted Au–Mo–Cu deposits.
Keywords: GRANITE; PERALKALINE; PORPHYRY; GOLD; ARSENIC; ISOTOPE; Cretaceous; Ordovician; Mesozoic::Cretaceous; Мезозой::Меловая; Paleozoic::Ordovician; Палеозой::Ордовикская